Characterization and Modeling of Electrochemical Energy Conversion Systems by Impedance Techniques - Klotz, Dino (Schriften des Instituts für Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Werkstoffe der Elektrotechnik, 2012)
This thesis introduces (i) amendments to basic electrochemical measurement techniques in the time and frequency domain suitable for electrochemical energy conversion systems like fuel cells and batteries, which enable shorter measurement times and improved precision in both measurement and parameter identification, and (ii) a modeling approach that is able to simulate a technically relevant system just by information gained through static and impedance measurements of laboratory size cells.